2021
DOI: 10.15421/012120
|View full text |Cite
|
Sign up to set email alerts
|

Virioplankton as an important component of plankton in the Volga Reservoirs

Abstract: The distribution of virioplankton, abundance and production, frequency of visibly infected cells of heterotrophic bacteria and autotrophic picocyanobacteria and their virus-induced mortality have been studied in mesotrophic and eutrophic reservoirs of the Upper and Middle Volga (Ivankovo, Uglich, Rybinsk, Gorky, Cheboksary, and Sheksna reservoirs). The abundance of planktonic viruses (VA) is on average by 4.6 ± 1.2 times greater than the abundance of bacterioplankton (BA). The distribution of VA in the Volga r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Global warming affects plant and animal communities across all climatic zones (Burda and Koniakin, 2019;Baranovski et al, 2020). Insect species with southern ranges move northward, where they find themselves in unsuitable climatic conditions at certain stages of their ontogenesis, although the average annual temperatures do not necessarily differ from those of their original range (Avtaeva et al, 2019;2021). Inconsistencies with the habitat conditions in a new FOLIA OECOLOGICA -vol.…”
Section: Introductionmentioning
confidence: 99%
“…Global warming affects plant and animal communities across all climatic zones (Burda and Koniakin, 2019;Baranovski et al, 2020). Insect species with southern ranges move northward, where they find themselves in unsuitable climatic conditions at certain stages of their ontogenesis, although the average annual temperatures do not necessarily differ from those of their original range (Avtaeva et al, 2019;2021). Inconsistencies with the habitat conditions in a new FOLIA OECOLOGICA -vol.…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometry analysis which revealed 3-fold higher standing stock of viruses and bacteria in the eutrophic than non-eutrophic lakes, was largely explained by the differences in the dissolved organic carbon and chlorophyll concentration [ 13 , 36 , 37 ]. A strong positive correlation of viral abundance with bacteria rather than with chlorophyll concentration pointed out the dominance of bacteriophages (viruses which infect bacteria) in the viral population.…”
Section: Discussionmentioning
confidence: 99%
“…Lytic infection, as evaluated from FVIC estimates (range: 1.0–4.1%) using the TEM approach, was comparable with literature reports from freshwater systems [ 40 , 41 , 42 ]. Our interpretation of viral-mediated bacterial mortality from FVIC by using the empirical models of Weinbauer et al [ 31 ] and Binder [ 32 ], which essentially relates to the bacteriophage infection cycle, suggested that between 7% and 76% of bacterial production was destroyed among the investigated lakes [ 12 , 13 , 43 ]. Two-fold higher estimates of viral lysis in the eutrophic compared with non-eutrophic lakes are suggestive of their relative importance in influencing bacterial communities, which are known to increase with trophic status [ 23 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has been revealed that nutrients, temperature, light, and hydrodynamic regimes are the key environmental factors affecting the outbreaking and succession of blooms ( Fang et al, 2013 ; Yang et al, 2022 ). As for viruses in reservoirs, Kopylov and Zabotkina (2021) investigated the distribution of viruses, the frequency of visibly infected cells of heterotrophic bacteria and autotrophic picocyanobacteria and their virus-induced mortality in six reservoirs along the Volga. The viral infection rate of picocyanobacteria in mesoeutrophic reservoir was higher than that in mesotrophic reservoir ( Kopylov et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%